The effects of marginal zinc deficiency on biochemical and physiological parameters in beef heifer and Holstein steer calves - Engle, Terry E., author; Nockels, Cheryl F., advisor; Kimberling, Cleon, committee member; Ward, Gerald M., committee member (Colorado State University. Libraries, 1996)
To view the abstract, please see the full text of the document.
Keywords: Trace elements in animal nutrition; Zinc deficiency diseases